The Development of the Silurian Trilobite Aulacopleura koninckii Reconstructed by Applying Inferred Growth and Segmentation Dynamics: A Case Study in Paleo-Evo-Devo - Hughes, Nigel C.; Hong, Paul S.; Hou, Jinbo; Fusco, Giuseppe (Frontiers in Ecology and Evolution, 2017)
Fossilized growth series provide rare glimpses into the development of ancient organisms, illustrating descriptively how size and shape changed through ontogeny. Occasionally fossil preservation is such that it is feasible to test alternative possibilities about how ancient development was regulated. Here we apply inferred developmental parameters pertaining to size, shape, and segmentation in the abundant and well-preserved 429 Myr old trilobite Aulacopleura koninckii that we have investigated previously to reconstruct the post-embryonic ontogeny of this ancient arthropod. Our published morphometric analyses associated with model testing have shown that: specification of the adult number of trunk segments (polymorphic in this species) was determined precociously in ontogeny; that growth regulation was targeted (i.e., compensatory), such that each developmental stage exhibited comparable variance in size and shape; and that growth gradients operating along the main body axis, both during juvenile and adult ontogeny, resulted from a form of growth control based on positional specification. While such developmental features are common among extant organisms, our results represent the oldest evidence for them within Metazoa. Herein, the novel reconstruction of the development of A. koninckii permits visualization of patterns of relative and absolute growth and segmentation as never before possible for a fossilized arthropod ontogeny. By conducting morphometric analysis of appropriate data sets it is thus possible to move beyond descriptive ontogenetic studies and to address questions of high interest for evolutionary developmental biology using data from fossils, which can help elucidate both how developmental processes themselves evolve and how they affect the evolution of organismal body patterning. By extending similar analyses to other cases of exceptional preservation of fossilized ontogeny, we can anticipate beginning to realize the research program of “paleo-evo-devo”.